Quantifying the risk of respiratory infection in healthcare workers performing high-risk procedures. (September 2014) - MACINTYRE, C. R.; SEALE, H.; YANG, P.; ZHANG, Y.; SHI, W.; ALMATROUDI, A.; MOA, A.; WANG, X.; LI, X.; PANG, X.; WANG, Q.
SUMMARY This study determined the risk of respiratory infection associated with high-risk procedures (HRPs) performed by healthcare workers (HCWs) in high-risk settings. We prospectively studied 481 hospital HCWs in China, documented risk factors for infection, including performing HRPs, measured new infections, and analysed whether HRPs predicted infection. Infection outcomes were clinical respiratory infection (CRI), laboratory-confirmed viral or bacterial infection, and an influenza infection. About 12% (56/481) of the study participants performed at least one HRP, the most common being airway suctioning (7·7%, 37/481). HCWs who performed a HRP were at significantly higher risk of developing CRI and laboratory-confirmed infection [adjusted relative risk 2·9, 95% confidence interval (CI) 1·42–5·87 and 2·9, 95% CI 1·37–6·22, respectively]. Performing a HRP resulted in a threefold increase in the risk of respiratory infections. This is the first time the risk has been prospectively quantified in HCWs, providing data to inform occupational health and safety policies.